Concealed Pulmonary Vein Bigeminy during Sinus Rhythm in Patients with Paroxysmal Atrial Fibrillation: A Useful Marker for Pulmonary Vein Firing - Jiqiang Hu; Wu Kuang; Xiaoyun Cui; Yan Li; Yang Wu; Qian Lin; Xuan Wang (Cardiology Research and Practice)
Introduction. A concealed pulmonary vein (PV) bigeminy (cPVB) may be found in some patients with atrial fibrillation (AF) during sinus rhythm (SR). The aim of this study was to investigate whether the presence of cPVB during SR is associated with a higher PV firing. Methods and Results. Seven hundred seventy-six PVs (excluding 5 right middle PVs and 8 left common trunks) were mapped in 198 patients with paroxysmal AF (PAF) who underwent circumferential PV isolation. cPVB with a mean coupling interval of 136 ± 16 ms during SR was observed prior to ablation in 22 (11%) patients. Focal firing was provoked prior to ablation in 144 (19%) PVs. The incidence of focal firing was greater in PVs exhibiting cPVB compared with PVs without cPVB (89% vs. 16%; P<0.001). Also, the number of radiofrequency applications required for isolation was greater in ipsilateral PVs, exhibiting cPVB compared with ipsilateral PVs without cPVB (21.6 ± 6.8 vs. 18.2 ± 5.6; P=0.024). During a follow-up of 32 ± 20 months, the single ablation success rate was 82%. Compared with patients without cPVB, patients with cPVB were associated with higher recurrence rate of AF (27% vs. 17%; p=0.032). Conclusion. cPVB during SR was observed prior to index ablation in 11% of PAF patients. Such a potential itself may be a PV firing in a concealed manner, which does not reactivate LA. The PV exhibiting cPVB required a greater number of radiofrequency applications for isolation. Compared to patients without cPVB, the recurrence rate of AF in patients with cPVB was greater.